2023
DOI: 10.1002/ps.7693
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing oviposition behaviour of the invasive pest, Drosophila suzukii, derived from interactions with other Drosophila species: potential applications for control

Abstract: Drosophila suzukii (Matsumura) or spotted wing Drosophila is a worldwide invasive pest of soft‐ and stone‐fruit production. Female D. suzukii lay their eggs in ripening fruit and the hatched larvae damage fruit from the inside, rendering it unmarketable and causing significant economic loss. Current methods to reduce D. suzukii population in the field primarily rely on chemical insecticides which are not a sustainable long‐term solution and increase the risk of resistance developing. Several studies demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 123 publications
0
4
1
Order By: Relevance
“…It was therefore expected that female flies would not be attracted by larvae from some Drosophila species, as some species combinations could be beneficial and others not ( Durisko, Anderson et al 2014 ). Studies have shown in the case of Drosophila suzukii that females are deterred to oviposit by the presence of D. melanogaster larvae, contrary to the behavior of the species we tested, which suggests that D. suzukii perceives D. melanogaster as a competitor species, modulating the oviposition choice ( Tungadi et al 2022 , 2023 ). Furthermore, our results suggest that D. melanogaster and D. mojavensis females do not distinguish between larvae of different species.…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…It was therefore expected that female flies would not be attracted by larvae from some Drosophila species, as some species combinations could be beneficial and others not ( Durisko, Anderson et al 2014 ). Studies have shown in the case of Drosophila suzukii that females are deterred to oviposit by the presence of D. melanogaster larvae, contrary to the behavior of the species we tested, which suggests that D. suzukii perceives D. melanogaster as a competitor species, modulating the oviposition choice ( Tungadi et al 2022 , 2023 ). Furthermore, our results suggest that D. melanogaster and D. mojavensis females do not distinguish between larvae of different species.…”
Section: Discussioncontrasting
confidence: 71%
“…Drosophilid flies are known to exhibit species-specific chemical cues which they use to communicate intra- and interspecifically ( Antony et al 1985 ; Bartelt et al 1985 ; Ferveur 2005 ; Yew et al 2009 ; Laturney and Billeter 2016 ; Khallaf et al 2021 ; Tungadi et al 2023 ). Here we described the chemistry of eggs, larvae, and mated females from 16 Drosophila species, and we found that the chemical profiles across the larvae species tested is more similar, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The split tomato from which many of these lines were obtained, may have been compromised on the vine by D.suzukii and followed by colonization from the other species. Given the extensive crop damage that invasive D.suzukii does (Tungadi et al 2023), it will be very important to explore the details of the advantages and disadvantages of clustering to this pest.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, H. uvarum plays an important role in the nutritional physiology, host attraction behaviour, oviposition and survival of D. suzukii (Bellutti et al, 2018;Mori et al, 2017;Scheidler et al, 2015;Tungadi et al, 2023). The presence of yeasts or yeast culture media in insecticide spray applications can result in an increase in the efficacy of several different classes of insecticides (Bianchi et al, 2020;Rehermann et al, 2022;Spitaler et al, 2022).…”
mentioning
confidence: 99%